2013
DOI: 10.1371/journal.pone.0061271
|View full text |Cite
|
Sign up to set email alerts
|

Antifatigue Effects of Panax ginseng C.A. Meyer: A Randomised, Double-Blind, Placebo-Controlled Trial

Abstract: The present study investigated the antifatigue effects of Panax ginseng C.A. Meyer in 90 subjects (21 men and 69 women) with idiopathic chronic fatigue (ICF) in a randomised, double-blind, placebo-controlled and parallel designed trial. A bespoke 20% ethanol extract of P. ginseng (1 g or 2 g day–1) or a placebo was administered to each group for 4 weeks, and then fatigue severity was monitored using a self-rating numeric scale (NRS) and a visual analogue scale (VAS) as a primary endpoint. Serum levels of react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
135
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(137 citation statements)
references
References 46 publications
1
135
0
1
Order By: Relevance
“…Our results confirm the results of previous studies using PG in noncancer populations. 17,52,53 Panax ginseng significantly improved QOL scores possibly as a result of its effects on CRF and related symptoms such as pain, sleep disturbances, and anorexia. Prior studies in animal models have shown that PG modulates proinflammatory cytokines [54][55][56] owing to the effects of the active ingredients such as ginsenosides and polysaccharides contained in the ginseng extract.…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm the results of previous studies using PG in noncancer populations. 17,52,53 Panax ginseng significantly improved QOL scores possibly as a result of its effects on CRF and related symptoms such as pain, sleep disturbances, and anorexia. Prior studies in animal models have shown that PG modulates proinflammatory cytokines [54][55][56] owing to the effects of the active ingredients such as ginsenosides and polysaccharides contained in the ginseng extract.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, natural products including ginseng have been studied with the aim of developing anti-fatigue drugs to improve athletic ability, delay fatigue, and enhance the elimination of fatigue in humans. [2][3][4][5][6] Ginseng (the root of Panax ginseng C.A. MEYER, Araliaceae) has been widely used as a traditional Chinese medicine for enhancing body strength, recovering physical balance, and stimulating metabolic function in Asian countries.…”
mentioning
confidence: 99%
“…Many investigators have found that ginseng may increase the duration of exercise to exhaustion during forced exercise trials [14,21]. In absence of experimental data, this was believed to be due to a general adaptogenic activity of ginseng supplementation [43].…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies the G115 extract exerted a dose dependent inhibition of the formation of free radicals in rats subjected to physical stress exercise on a treadmill [20]. A clinical study [21] suggests that the beneficial effect of 4 weeks ginseng administration observed in patients with idiopathic chronic fatigue (ICF) may be partly attributed to its antioxidant properties, and oxidative stress is considered as a main contributor to the pathology of chronic fatigue [22]. Moreover, animal studies with the extract G115 show enhancement of glucose transportation in the cells [23], and its pre-treatment increased the production of the Toll like receptor 4 in mice during physical stress [10].…”
Section: Introductionmentioning
confidence: 99%